A flexible, preclinical, medical school curriculum increases student academic productivity and the desire to conduct future research. Issue 5 (6th July 2015) - Peacock, Justin G.; Grande, Joseph P.
Abstract: In 2006, small blocks of flexible curriculum time, termed selectives, were implemented in the Mayo Medical School preclinical curriculum. Selectives permitted students to pursue professional endeavors, such as research, service, and career exploration, in the preclinical years. The purpose of this study was to survey current and former Mayo medical students regarding the impact of selectives on their research interest and productivity. The authors surveyed 377 current and former Mayo Medical School students from the 2004 to 2014 graduating classes, 154 participants (41% response rate) responded to the survey. The classes were grouped into pre‐ and postselective groups for the comparison studies. Postselective students published significantly more ( p  = 0.003) and gave significantly more presentations ( p  = 0.0007) during medical school than preselective students. Thirty‐four (72% of the postselective respondents) indicated that selectives had a strong or very strong impact on their current research interest. Respondents spent an average of 4.0 [3.0–5.0] weeks of Selective time on research, resulting in 1.8 [1.4–2.2] publications and 1.8 [1.4–2.2] presentations, which represented 52.5% [40.0–65.0%] and 47.3% [37.1–57.4%] of the students' total medical school publications and presentations, respectively. Flexible selective time during the preclinical years results in significantly more medical student academic productivity. © 2015 by The International Union of Biochemistry and Molecular Biology, 43(5):384–390, 2015.